The impact of liquidity on the financial succes of agricultural enterprises - Ševkušić Ljubiša; Bodiroga Radomir (Megatrend Revija)
It is often pointed out in the literature that liquidity is one of the key determinants of a company's success. However, the impact of liquidity is not the same for all economic entities, but it largely depends on the activity in which the company is engaged. In this regard, the main preoccupation of this paper is to examine the effects of liquidity on the financial results of enterprises in the agricultural sector of Serbia. In addition to simple correlation and regression analysis, the paper used methods of parsing and comparison, as well as methods of analysis and synthesis. The results of the research clearly show that there is a weak positive correlation between liquidity and financial results of agricultural enterprises in Serbia, ie. that liquidity doesn't significantly determine the success of these companies.